The Impact of Learning by Doing Application to Enhance Students Inquiry in The Classroom - Vimala Murti (CV. Green Publisher Indonesia, 2021)
Background: Learning by doing, also known as experiential learning, is a method when the learners actively participate in the learning process. The role of the teacher is to guide and facilitate the learners by providing a variety of activities and teaching materials that enhance inquiry in the classroom.Research purposes: The purpose of this study was aimed to investigate the impact of learning by doing applications to enhance students‟ inquiry in the classroom.Research methods: The present study involved forty-six (46) teachers across disciplines. Literature review, teachers‟ questionnaires, and open-ended questions through interviews were used for this study.Research results: The finding showed that most of the respondents understood and agreed about the impact of learning by doing application in the classroom and have been applied the method in their teaching and learning process. Some strategies, strengths, and possible challenges were shared during the interview. Hence, the result emphasized that the method enhances active participation that promotes inquiry.Conclusion: Most of teachers are familiar and consistently implement the learning by doing strategies to extend inquiry in the classroom. Some of the learning by doing strategies were shared during the interview. Most of the teachers have occupied with professional development workshops to increase their understanding on how to implement learning by doing that enhance inquiry in the classroom practices. Accordingly, over 90% of teachers agreed on the importance of application learning by doing in the classroom practices. Regarding some feedback, more than half of teachers agreed that learning resources and environment are helpful in the application of learning by doing. Moreover, learning by doing also enhanced inquiry and promote student voice and choice. Despite all the strengths have mentioned above, some challenges also were shared. For example limited resources, time and cost consume and different teachers' abilities in applying learning by doing in the classroom